Impacts of public health and social measures on COVID-19 in Europe: a review and modified Delphi technique - Paulo, Marília Silva; Peyroteo, Mariana; Maia, Mélanie R.; Pries, Cara; Habl, Claudia; Lapão, Luís Velez (Frontiers in public health, 2023)
The emergence of the COVID-19 pandemic in early 2020 led countries to implement a set of public health and social measures (PHSMs) attempting to contain the spread of the SARS-CoV-2 virus. This study aims to review the existing literature regarding key results of the PHSMs that were implemented, and to identify the PHSMs considered to have most impacted the epidemiological curve of COVID-19 over the last years during different stages of the pandemic.IntroductionThe emergence of the COVID-19 pandemic in early 2020 led countries to implement a set of public health and social measures (PHSMs) attempting to contain the spread of the SARS-CoV-2 virus. This study aims to review the existing literature regarding key results of the PHSMs that were implemented, and to identify the PHSMs considered to have most impacted the epidemiological curve of COVID-19 over the last years during different stages of the pandemic.The PHSM under study were selected from the Oxford COVID-19 Government Response Tracker (OxCGRT), supplemented by topics presented during the Rapid Exchange Forum (REF) meetings in the scope of the Population Health Information Research Infrastructure (PHIRI) project (H2020). The evidence- based review was conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines to identify which reviews have already been published about each PHSMs and their results. In addition, two modified Delphi panel surveys were conducted among subject matter experts from 30 European countries to uphold the results found.MethodsThe PHSM under study were selected from the Oxford COVID-19 Government Response Tracker (OxCGRT), supplemented by topics presented during the Rapid Exchange Forum (REF) meetings in the scope of the Population Health Information Research Infrastructure (PHIRI) project (H2020). The evidence- based review was conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines to identify which reviews have already been published about each PHSMs and their results. In addition, two modified Delphi panel surveys were conducted among subject matter experts from 30 European countries to uphold the results found.There were 3,212 studies retrieved from PubMed, 162 full texts assessed for eligibility and 35 included in this PHSMs summary. The measures with clearest evidence on their positive impact from the evidence-based review include social distancing, hygiene measures, mask measures and testing policies. From the modified Delphi panel, the PHSMs considered most significant in the four periods analyzed were case isolation at home, face coverings, testing policy, and social distancing, respectively.ResultsThere were 3,212 studies retrieved from PubMed, 162 full texts assessed for eligibility and 35 included in this PHSMs summary. The measures with clearest evidence on their positive impact from the evidence-based review include social distancing, hygiene measures, mask measures and testing policies. From the modified Delphi panel, the PHSMs considered most significant in the four periods analyzed were case isolation at home, face coverings, testing policy, and social distancing, respectively.The evidence found has significant implications for both researchers and policymakers. The study of PHSMs' impact on COVID-19 illustrates lessons learned for future pan- and epidemics, serving as a contribution to the health systems resilience discussion. These lessons, drawn from both the available scientific evidence and the perspectives of relevant subject matter experts, should also be considered in educational and preparedness programs and activities in the public health space.DiscussionThe evidence found has significant implications for both researchers and policymakers. The study of PHSMs' impact on COVID-19 illustrates lessons learned for future pan- and epidemics, serving as a contribution to the health systems resilience discussion. These lessons, drawn from both the available scientific evidence and the perspectives of relevant subject matter experts, should also be considered in educational and preparedness programs and activities in the public health space.